2008
DOI: 10.1089/tea.2007.0245
|View full text |Cite
|
Sign up to set email alerts
|

In SituCrosslinking Elastin-Like Polypeptide Gels for Application to Articular Cartilage Repair in a Goat Osteochondral Defect Model*

Abstract: The objective of this study was to evaluate an injectable, in situ crosslinkable elastin-like polypeptide (ELP) gel for application to cartilage matrix repair in critically sized defects in goat knees. One cylindrical, osteochondral defect in each of seven animals was filled with an aqueous solution of ELP and a biocompatible, chemical crosslinker, while the contralateral defect remained unfilled and served as an internal control. Joints were sacrificed at 3 (n = 3) or 6 (n = 4) months for MRI, histological, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…In addition, the integrity and survival of THPP-crosslinked ELPs following injection into a tissue site in a goat model were evaluated as injectable hydrogels for articular cartilage repair of an osteochondral defect. 56 We observed that the solution mixture of THPP and ELP became turbid within one minute solid after 5 minutes. Thus, all surgical sites were closed at 5 minutes after injection into the cartilage defect site.…”
Section: Chemical Cross-linking Of Elpsmentioning
confidence: 77%
“…In addition, the integrity and survival of THPP-crosslinked ELPs following injection into a tissue site in a goat model were evaluated as injectable hydrogels for articular cartilage repair of an osteochondral defect. 56 We observed that the solution mixture of THPP and ELP became turbid within one minute solid after 5 minutes. Thus, all surgical sites were closed at 5 minutes after injection into the cartilage defect site.…”
Section: Chemical Cross-linking Of Elpsmentioning
confidence: 77%
“…ELPs could be enzymatically crosslinked by transglutaminase to form elastic gels with improved mechanical properties but the clinical applications of these gels was hampered due to the length of time required for the crosslinking reaction to take place [88]. To solve this problem, Setton and Chilkoti synthesized an ELP containing lysine, ELP[V 6 K 1 -224], which could chemically crosslink in less than 5 min by using β-[tris(hydroxymethyl)phosphino]propionic acid (THPP) as a crosslinking agent under physiological conditions [8992]. The fabricated hydrogel was injected into an osteochondral defect in a goat model.…”
Section: Elastin As a Biomaterials For Tissue Engineeringmentioning
confidence: 99%
“…Often additional chemical crosslinking schemes have been used to form more rigid and stable gels. For example, elastin-like protein polymers have been chemically crosslinked by tris-succinimidyl aminotriacetate [14], disuccinimidyl suberate [15], and hydroxymethylphosphine crosslinking chemistries [16], greatly improving gel mechanical properties. Chemical crosslinking, however, is not ideal for in situ gelation due to possible crosslinker toxicity in vivo .…”
Section: Introductionmentioning
confidence: 99%